Coumarins and Gastrointestinal Cancer: A New Therapeutic Option? - Banikazemi, Zarrin; Mirazimi, Seyed Mohammad; Dashti, Fatemeh; Mazandaranian, Mohammad Reza; Akbari, Maryam; Morshedi, Korosh; Aslanbeigi, Fatemeh; Rashidian, Amir; Chamanara, Mohsen; Hamblin, Michael R.; Taghizadeh, Mohsen; Mirzaei, Hamed (Frontiers in Oncology, 2021)
Cancers of the gastrointestinal (GI) tract are often life-threatening malignancies, which can be a severe burden to the health care system. Globally, the mortality rate from gastrointestinal tumors has been increasing due to the lack of adequate diagnostic, prognostic, and therapeutic measures to combat these tumors. Coumarin is a natural product with remarkable antitumor activity, and it is widely found in various natural plant sources. Researchers have explored coumarin and its related derivatives to investigate their antitumor activity, and the potential molecular mechanisms involved. These mechanisms include hormone antagonists, alkylating agents, inhibitors of angiogenesis, inhibitors of topoisomerase, inducers of apoptosis, agents with antimitotic activity, telomerase inhibitors, inhibitors of human carbonic anhydrase, as well as other potential mechanisms. Consequently, drug design and discovery scientists and medicinal chemists have collaborated to identify new coumarin-related agents in order to produce more effective antitumor drugs against GI cancers. Herein, we summarize the therapeutic effects of coumarin and its derivatives against GI cancer.